Determining the Effect of Process Parameters on Surface Roughness in two Point Incremental Sheet Metal Forming Process using the Taguchi Method - Harith Yarub Maan (Engineering and Technology Journal, 2015)
The main aim of this study is determining the effect of process parameters on surface roughness in two-point incremental sheet metal forming process using the Taguchi method. The experimental plan and analysis were basedon the mixed L18 Taguchi orthogonal array withfour forming parameters, tool radius (r), feed rate (f), stepover (Δz) and type of support (full and partial support) were analyzed andpyramid shape was used (57°) wall angle. The influence of the process parameters has been investigated and optimum forming condition for minimizing the surface roughness is evaluated. The analysis results show that the stepover has the highest effect on the surface roughness and followed by tool radius, feed rate and die.The result shows that the errorof predicted accuracy for the surface roughness is (1.2%).